Full-length sucrose-formulated recombinant factor VIII for treatment of previously untreated or minimally treated young children with severe haemophilia A - Kreuz, Wolfhart; Gill, Joan C.; Rothschild, Chantal; Manco-Johnson, Marilyn J.; Lusher, Jeanne M.; Kellermann, Elke; Gorina, Eduard; Larson, Peter J.; and the International Kogenate-FS Study Group (Thrombosis and Haemostasis, 2005)
The safety and efficacy of a full-length sucrose-formulated recombinant factor VIII product (rFVIII-FS; KogenateFS; Kogenate Bayer) was evaluated in previously untreated (PUPs) and minimally treated (MTP) patients with severe haemophilia A (FVIII < 2%). Patients (37 PUPs; 24 MTPs) aged 0.1–25.7 months were treated with rFVIII-FS for a cumulative of 9,141 exposure days (EDs), median 114 EDs (range 4–478), on prophylactic or on-demand therapy. Eighty-nine percent of all treated bleeding episodes were successfully treated with 1 (74%) or 2 (15%) infusions. Clinical response to first infusion for each bleeding episode was rated as ‘excellent’ in 58%, or ‘good’ in 33%, of all cases. Recombinant FVIII-FS was used in 27 surgical procedures, mainly catheter implantations, which were all conducted without bleeding complications. FVIII recovery mean values (~2%/kg/ IU) were as expected for any licensed FVIII concentrate. FVIII neutralizing antibody formation was 15% (9/60). Aside from inhibitor formation, three adverse events were rated as ‘at least possibly drug-related’ for a total drug-related adverse event rate of 0.14%. No viral seroconversions were observed. Overall, excellent safety and efficacy were demonstrated with rFVIII-FS for therapy of young children with severe haemophilia A.
Keywords: Haemophilia A; FVIII inhibitor; pediatric; PUPs